Prostate cancer diagnostics: evolution over 30 years and the impact of education level – a prospective population-based study - Will, Leon; Thimansson, Erik; Bengtsson, Johan; Bjartell, Anders; Zackrisson, Sophia; Baubeta, Erik (Frontiers in Oncology, 2025)
ObjectiveThe aim of this study is to describe how the use of diagnostic imaging for prostate cancer (PCa) has evolved over time and to determine whether there are any differences in access to diagnostic imaging, type of cancers detected, and mortality based on the education level of patients.Methods11,063 men were recruited between 1991 and 1996 and then prospectively followed until 2020. All new cases of PCa were recorded. At baseline, data on education level, heredity for cancer, and health status were collected. Incident PCa diagnoses during the study period were ascertained through record matching with national healthcare registers. The registers provided more detailed data on the cancer type and imaging performed.Results1,816 men with diagnosed were PCa during the study period were included. No differences were seen between education levels in regard to access to diagnostic methods or tumour aggressiveness at diagnosis. Furthermore, no differences were seen in PCa-specific mortality, but there was higher overall mortality among individuals with a lower education level. During the study period, the use of plain radiographic examinations decreased, while the use of computed tomography (CT), prostate magnetic resonance imaging (MRI), and positron emission tomography/computed tomography (PET/CT) increased.ConclusionEarly detection and diagnostic methods for PCa have evolved over the last 30 years. In a healthcare system where men diagnosed with PCa had equal access to diagnostic pathways, no differences are seen in PCa specific mortality. Nevertheless, men with lower education level still had higher overall mortality.